PERENCANAAN DAN STRATEGI KOMUNIKASI JARINGAN FRANCHISE WARUNG TEGAL KHARISMA BAHARI - Agus Hitopa Sukma; Iswahyu Pranawukir (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
In Jakarta, the image of the Tegal warung which is synonymous with the lower-class consumer segmentation has slowly begun to change, since the Kharisma Bahari franchise has begun to offer a new concept in the tegal shop business. This shop has tried digital services to improve its consumer segmentation services. The research objective is to know the planning and communication strategy of the Warung Tegal Kharisma Bahari (WTKB) franchise network in increasing consumer segmentation. The research method is descriptive qualitative and the interview process is carried out through data classification and cross check theory. The results showed that there was a dynamic communication strategy of the WTKB franchise network in increasing the resources of WTKB actors. At the initial stage the pull model is used, then the push model, followed by the pass. Pull, by accommodating all the aspirations and inspirations of WTKB actors to find a solution, while push, a cultural change communication strategy sells through the 5R messages: Concise, Neat, Clean, Careful and Diligent. Communication barriers include cultural, educational and personal aspects. While the supporting aspect is the operational field of WTKB which has been attached to all levels of society as a traditional cheap food which is a cost-effective solution.